Cognitive, Social-Emotional, Religious, and Moral Development in Childhood And Adolescence - Andita Dwi Puspitaningsih; Yustia Rachma Fitriani; Hamam Burhanuddin (Civiliza Publishing, Indonesia., 2026)
This study aims to describe cognitive, social-emotional, religious, and moral development during childhood and adolescence. The research employs a qualitative approach with a descriptive design and utilizes a literature review method by collecting data from books, journals, and relevant scientific sources. The findings indicate that cognitive development from childhood to adolescence progresses from concrete to abstract thinking, influenced by biological maturation and social interaction. Social-emotional development is characterized by an increased ability to manage emotions, build social relationships, and form identity, particularly during adolescence. Meanwhile, religious and moral development shows a shift from rule-based understanding toward deeper and more independent internalization of values. These four aspects of development are interrelated and influenced by internal factors, family, school, and the social environment. Therefore, the roles of parents, teachers, and the environment are crucial in supporting optimal development in children and adolescents.